Review of Ptycholaimellus Cobb (Nematoda, Chromadoridae), with descriptions of three species - Jensen, P.; Nehring, S. (Zoologica Scripta, 1992)
Nematodes of the genus Ptycholaimellus Cobb, 1920 are unique in possessing a collar by which the head is separated from the body. The collar is raised from a groove at the border between the neck and the remainder of the body. The contents of the ventral gland cell are emptied in the groove in at least 9 out of 14 species. It is suggested that the amphids arc located in the groove. Fourteen species are considered to belong to Ptycholaimellus. Two Ptycholaimellus species are described as new to science, that is, P. jacobi sp.n. and P. vincxae sp.n.; P. ponticus (Filipjcv, 1922) is redescribed. Ptycholaimellus ponticus sensu Stekhoven (1950) and Boucher (1972) from the Mediterranean off France differs from the other Ptycholairmellus species by its subcuticular ornamcntation and shape of spicules, hence these specimens are regarded as belonging to a new species: Ptycholaimellus boucheri sp.n. Chromadorissa inaequibulba Aminova & Galtsova, 1978 is transferred to Ptycholaimellus as P. inaequibulbus. Ptycholaimellus ponticus from Europe and P. pandispiculatus (Hopper, 1961) from the east coast of North Amcrica are assumed to have colonized brackish waters independently.
Locality: ; Cabinet:n160 NeMys doc_id: 16815